Physical fitness reference standards for preschool children: The PREFIT project. Issue 4 (April 2019) - Cadenas-Sanchez, Cristina; Intemann, Timm; Labayen, Idoia; Peinado, Ana B.; Vidal-Conti, Josep; Sanchis-Moysi, Joaquin; Moliner-Urdiales, Diego; Rodriguez Perez, Manuel A.; Cañete Garcia-Prieto, Jorge; Fernández-Santos, Jorge del Rosario; Martinez-Tellez, Borja; Vicente-Rodríguez, Germán; et al.
Abstract: Objectives: Reference values are necessary for classifying children, for health screening, and for early prevention as many non-communicable diseases aggravate during growth and development. While physical fitness reference standards are available in children aged 6 and older, such information is lacking in preschool children. Therefore, the purposes of this study were (1) to provide sex-and age-specific physical fitness reference standards for Spanish preschool children; and (2) to study sex differences across this age period and to characterise fitness performance throughout the preschool period. Design: Cross-sectional. Methods: A total of 3179 preschool children (1678 boys) aged 2.8–6.4 years old from Spain were included in the present study. Physical fitness was measured using the PREFIT battery. Results: Age- and sex-specific percentiles for the physical fitness components are provided. Boys performed better than girls in the cardiorespiratory fitness, muscular strength, and speed-agility tests over the whole preschool period studied and for the different percentiles. In contrast, girls performed slightly better than boys in the balance test. Older children had better performance in all fitness tests than their younger counterparts. Conclusions: Our study provides age- and sex-specific physical fitness reference standards in preschool children allowing interpretation of fitness assessment. Sexual dimorphism in fitness tests exists already at preschool age, and these differences become larger with age. These findings will help health, sport, and school professionals to identify preschool children with a high/very low fitness level, to examine changes in fitness over time, and to analyse those changes obtained due to intervention effects.